2015
DOI: 10.1038/nnano.2015.79
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled quantum light from an atomically thin semiconductor

Abstract: Although semiconductor defects can often be detrimental to device performance, they are also responsible for the breadth of functionality exhibited by modern optoelectronic devices. Artificially engineered defects (so-called quantum dots) or naturally occurring defects in solids are currently being investigated for applications ranging from quantum information science and optoelectronics to high-resolution metrology. In parallel, the quantum confinement exhibited by atomically thin materials (semi-metals, semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

54
697
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(762 citation statements)
references
References 34 publications
54
697
10
1
Order By: Relevance
“…Hence, the energy of defect excitons is only slightly lower than that of free excitons, which is consistent with the low temperature photoluminescence spectra. The energy of defect excitons also matches well with that from SQEs observed in the WSe 2 monolayer, suggesting the tungsten vacancy defect to be a candidate of such emitters [20][21][22][23]. According to previous studies, the SQEs are subject to the circularly polarized optical selection rule, especially under high magnetic field.…”
Section: Prl 119 046101 (2017) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 72%
See 1 more Smart Citation
“…Hence, the energy of defect excitons is only slightly lower than that of free excitons, which is consistent with the low temperature photoluminescence spectra. The energy of defect excitons also matches well with that from SQEs observed in the WSe 2 monolayer, suggesting the tungsten vacancy defect to be a candidate of such emitters [20][21][22][23]. According to previous studies, the SQEs are subject to the circularly polarized optical selection rule, especially under high magnetic field.…”
Section: Prl 119 046101 (2017) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 72%
“…Moreover, in conjunction with giant spin-orbit splitting and spin-valley locking at the valence band, p-type doping facilitates the manipulation of valley coherence for a more extended time to 1-10 ns [17,18], in comparison to ∼10 ps with n-type doping [19]. More interestingly, when the WSe 2 monolayer is cooled below ∼10 K, the defectrelated localized exciton emissions behave as single quantum emitters (SQEs) [20][21][22][23], which are essential for quantum information processing [9]. Nevertheless, very little is known about the atomic and electronic structures of the defects in the WSe 2 monolayer.…”
mentioning
confidence: 99%
“…Our scheme for valley pseudospin manipulation should also extend to the recently discovered quantum-confined states of excitons in TMDC layers [29][30][31][32][33] . For these localized excitonic states, the valley pseudospin degree of freedom is expected to be well preserved 34 , but their lifetimes are far longer than for the free excitons examined in this work.…”
mentioning
confidence: 97%
“…[6][7][8][9] In particular, defect-derived excitonic states have recently received much attention for their applications in single-photon emitters. To date, several groups have reported that atomic-layer TMDCs show photoluminescence (PL) from optically active defects at low temperature (4 ∼ 90 K).…”
mentioning
confidence: 99%